2015
DOI: 10.1039/c4ta06674j
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature sequential ionic deposition (SID) of Ag2S nanoparticles on TiO2 hierarchical spheres for enhanced catalytic efficiency

Abstract: Porous TiO 2 hierarchical spheres with high surface area synthesized via a solvothermal method were successfully modified with an Ag 2 S co-catalyst by a sequential ionic deposition (SID) method at room temperature. The presence of Ag 2 S facilitated efficient charge separation, thus reducing recombination and enhancing the photocatalytic activity of the photocatalyst. The enhanced photocatalytic performance was demonstrated by water splitting where hydrogen (H 2 ) gas was produced at an evolution rate of 708 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 34 publications
1
31
1
2
Order By: Relevance
“…The broader absorption spectrum and lower absorption edge energy indicated that the ZnO–Sn 2 S 3 nanorod heterostructures had superior optical absorption capability under light illumination. It has been reported that the construction of a heterostructure by coupling with the visible light sensitizers similarly extended the optical absorption edge of the wide-bandgap oxides in other material systems (i.e., ZnO–CdS, TiO 2 –Ag 2 S, and SnO 2 –Fe 2 O 3 ) [2325]. Figure 4b displays the room-temperature PL spectra of the ZnO and ZnO–Sn 2 S 3 nanorods.…”
Section: Resultsmentioning
confidence: 87%
“…The broader absorption spectrum and lower absorption edge energy indicated that the ZnO–Sn 2 S 3 nanorod heterostructures had superior optical absorption capability under light illumination. It has been reported that the construction of a heterostructure by coupling with the visible light sensitizers similarly extended the optical absorption edge of the wide-bandgap oxides in other material systems (i.e., ZnO–CdS, TiO 2 –Ag 2 S, and SnO 2 –Fe 2 O 3 ) [2325]. Figure 4b displays the room-temperature PL spectra of the ZnO and ZnO–Sn 2 S 3 nanorods.…”
Section: Resultsmentioning
confidence: 87%
“…used sequential ionic deposition to fabricate Ag 2 S NPs on TiO 2 hierarchical spheres. Enhanced simulated solar light driven photocatalytic performance was demonstrated by water splitting with hydrogen production at 708 μmolh −1  g −1 and photodegradation of methyl orange with pseudo-first order rate constant of 0.018 min −1   39 .…”
Section: Introductionmentioning
confidence: 99%
“…Immobilisation of the TiO 2 film simplifies the separation of the photocatalystp ost-use, and reducest he chance that any nanoscale materials will remain in solution-a health risk which has recently been broughtt oa ttentioni nt he literature. [34][35][36][37] While BiOI SILAR for photovoltaica pplicationsh as been previouslys tudied, [38][39][40] to the BiOI nanoplates were deposited upon af ilm of TiO 2 nanoparticles derived from ac ommercial source using as imple room temperature sequential ionic layer adsorption and reaction (SILAR) method.X -ray diffraction, X-ray photoelectron spectroscopy and electron microscopies have been used to confirm the crystal phase, chemical states of key elements and morphologyofthe BiOI nanoplate-TiO 2 composites. [31][32][33] For the purposes of photocatalysis SILARi sr elatively unexplored and relatively few examples have been reported.…”
Section: Introductionmentioning
confidence: 99%